Pengaruh Penggunaan Media Baamboozle Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 6 Medan - Sihite, Debora Magdalena; Saragih, Elza L.L; Sianturi, Monalisa Frince (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to determine the effect of using Baamboozle media on the descriptive text writing skills of seventh-grade students at SMP Negeri 6 Medan in the 2024/2025 academic year. The research method used was quantitative with an experimental design. The sample consisted of randomly selected seventh-grade students. Data were collected through descriptive text writing tests before and after the Baamboozle treatment. The results showed a significant difference between students’ descriptive text writing skills before and after using Baamboozle media. This indicates that the use of Baamboozle media has a positive effect on students’ descriptive text writing skills. Therefore, Baamboozle media can be used as an alternative learning medium to improve students’ descriptive text writing skills.